COVID-19 Contagion Risk in Border Regions: A Case of Busia One-Stop Border Post Inefficiencies in Clearing Truckers - Omillo, Francis Okumu; Sibeyo, David (African Journal of Education,Science and Technology (AJEST), 2021)
Truckers are known to exacerbate emergence and spread of contagious diseases across borders. This study aims at investigating the implementation of COVID-19 prevention and control measures at Busia One-Stop Border Posts and its contribution to community spread of COVID-19. The study is anchored on viral-epidemiological theory and descriptive design. The research employed naturalistic observation and desk review techniques. Using google search engines, novel data streams containing google flu trends and epidemiological journal articles were accessed. The internet also enabled access to the Ministry of Health fact sheets, books and reports. The study found lengthy turnaround time for truckers due to unharmonised and uncorordinated implementation of COVID-19 prevention and control measures, poor infrastructure such as truck parking space, the intermittent supply of test kits and PPEs at points of entry and exit control. This resulted in congestion and mingling at Busia border post creating a ‘perfect storm’ for the contagious COVID-19 diffusion into the local community. Besides developing infrastructure, the study recommends One Stop Border Posts (OSBPs) to leverage on emergent technologies such as genomics, truck scanners, and digital systems for data capturing. Smartphones and social media provide a good option for contact tracing, too. In addition, to integrate COVID-19 protocols in one window customs clearance system built on trust of member states. Finally, the East Africa customs union should support building capacities of officers responsible for immigration, health and trade at Busia OSBP.